A word of caution: diabolic behaviour of AndraStents®: inflation of supporting balloon leads to "diabolo"-misconfiguration of the stent. (20th June 2019) - Happel, Christoph M.; Zunzunegui Martínez, Jose L.; del Cerro, María Jesús; Schranz, Dietmar; Khalil, Markus; Ballesteros, Fernando; Pardeiro, César Abelleira; Bertram, Harald; Beerbaum, Philipp; Haas, Nikolaus A.
Abstract: Aims: Transcatheter implantation of pulmonary balloon-expandable stent-valves requires pre-stenting of the right ventricular outflow tract with large calibre stents. To increase awareness of the associated risks of this part of transcatheter pulmonary valve replacement therapy, we report potential fatal complications during the implantation of AndraStents® in the right ventricular outflow tract in six cases from five different European institutions and their management. Method and result: We present a retrospective case series analysis looking at the time period from 2013 to 2018. Of 127 AndraStents® implanted in the right ventricular outflow tract, in six patients, age from 13 to 71 years, a misconfiguration of the AndraStent® occurred forming a "diabolo"-configuration. During inflation of the balloon, the stent showed extreme "dog-boning", an expansion of the stent at both ends with the middle part remaining unexpanded. This led to rupture of the balloon and loss of manoeuvrability in four patients. Out of the total six cases, in four patients the stent was eventually expanded with high-pressure balloons, and in one case the stent was surgically retrieved. In one patient, in whom a percutaneous retrieval of the embolised stent was attempted, a fatal bleeding occurred. Conclusions: Pre-stenting of the right ventricular outflow tract by AndraStents® can lead to misconfiguration of the stent with potentially fatal complications. Rescue strategies of misconfigured stents include stent inflation and placement with high pressure non-compliant balloons or surgical backup. Interventional retrieval measures of AndraStents® cannot be advised.